First-Order Regular and Degenerate Identification Differential Problems - A. Favini; A. Lorenzi; H. Tanabe (Abstract and Applied Analysis)
We are concerned with both regular and degenerate first-order identification problems related to systems of differential equations of weakly parabolic type in Banach spaces. Several applications to partial differential equations and systems will be given in a subsequent paper to show the fullness of our abstract results.